Social skills and habits students study in high school 5th year in a public school Chosica - Lima - Cunza Aranzábal, Denis Frank (2019)
Objective: Determine if there is statistically significant relation between social skills and study habits in fifth gradestudents. Methods: The research corresponds to a non-experimental, cross-sectional and correlational descriptivebecause they sought to find the relationship between social skills and study habits in high school students in apublic school Chosica - Lima. The participants were all students of the fifth year of high school in a public school,aged between 16 and 19. Two instruments were used, the Social Skills Checklist Mental Health Institute HonorioDelgado - Hideyo Noguchy (2005) and Study Habits Inventory Vicuña CASM 85 (2005). Results: Was found inthe level of social skills that 20% of students tested showed an average level, 26% presented a very low level and7% have a very high level, also 18% of the student population have an average level of study habits, 54% havea very low level, and 4% have a high level of study habits. It was also found that there is a relationship (p <.01)in terms of communication skills and general technical methods of study, performance of work, with preparationof exams, with notes in class, and accompanied the study. Also, there is a relationship between self-esteem andgeneral methods and techniques of study, and between self-esteem and class notes. Finally there is a relationshipbetween decision and performing work as well as with class notes. Conclusion: There is a significant correlationcoefficient (p <0.01), positive from weak to middle between social skills and study habits.